Paranasal sinus mucocele with visual disturbances whose causative legion was hardly identified on computed tomography imaging: A case report. Issue 1 (1st January 2019) - Mizushima, Yu; Mumo, Takashi; Yasui, Takuya; Ito, Ken
Abstract: We report one case of sinus mucocele with vision loss hardly identified on CT, resulting in diagnosis delay. A 34-year-old man was referred to the department of ophthalmology in our hospital because of acute loss of his left vision since morning of the day. Left compressive optic neuropathy was suspected and CT was performed. However, CT did not clearly show its causative legion. The patient went home without receiving any therapy. After that, the patient's vision was further damaged. MRI revealed the cystic lesion around the left anterior clinoid process which eroded left optic canal bone. Emergency surgery was performed, and both its cyst and optic nerve canal were opened endoscopically. After surgery, his left visual acuity was improved immediately. In conclusion, an MRI scan or the combination of CT and MRI modalities might be more useful for early and accurate diagnosis of paranasal sinus disease with visual disturbances.